All opinions are not equal: Toward a consensual approach to the development of drug policy. Issue 4 (18th April 2022) - Wong, Gabriel T. W.; Manning, Matthew
Abstract: Drug policy has been subjected to much scrutiny from different stakeholder groups who present sometimes very different opinions on solutions to address a problem. Reconciling such differences, that are underpinned by both anecdotal and empirical evidence, is a priority yet to be fully achieved. In this study, we examine: (i) whether differences exist among actor groups regarding their perceived importance in policymaking; (ii) whether those who dominate the decision process value the input of laypeople or minority actors; and (iii) whether differences exist, with regard to i and ii, between study sites (i.e. Australia and Hong Kong) that have markedly different drug strategies. Overall, differential preference weightings between dominant groups reveal a strong influence of political orientation. Results suggest that decisions made by health professionals were regarded as the most important, while most of the respondent groups gave a low preference toward policy decisions made by law enforcers. Dominant groups also tend to discount the inputs of laypeople and other minority groups. Our study highlights the importance for policy actor groups to consider such a differential weighting of inputs when synthesising knowledge and gathering opinions for the development of drug policy.